Development of retrogradation-resistant sterilized Biko as disaster food - Tanlimco, Alyana Marie C. (College of Home Economics, University of the Philippines Diliman, 2018)
Disaster prone countries such as the Philippines lack a variety of safe food during times of calamities. In this study, biko, a traditional Filipino rice cake, was developed into a ready-to-eat, sterilized disaster food. Product development was done by conducting preference ranking for base recipe selection followed by initial prototyping, focus group discussions, and final prototyping. Results from focus group discussions with disaster victims showed that the initial prototype is potentially suited to be a disaster food. The physical and sensory properties of the prototype and commercially-available samples were considered similar, although the prototype needs to be more firm and less messy. The resulting final prototype, after incorporating suggestions from the focus group discussions, was made from glutinous rice (28.1%), coconut milk (30.3%), water (20.8%), brown sugar, (13.7%), salt (0.1%), and vanilla extract (0.1%), arranged into 70g squares and packaged in banana leaf boxes on aluminum trays inside retortable pouches, which were sterilized at 250⁰F (F0=48). Physico-chemical tests were used to characterize the final prototypes moisture content (60.68), water activity (0.81), pH (5.52) and L*a*b color values (43.51, 8.99, 31.66, respectively), while commercial sterility tests were done to assure adequacy of the thermal process. Overall, the developed commercially-sterile biko was considered acceptable in terms of safety, physical and sensory characteristics. Further studies may explore validating the final prototype, using different packaging materials, and monitoring textural changes of the product during storage.